2015
DOI: 10.1007/s40195-015-0309-6
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Diffusion Layer During Passive Film Breakdown on Alloy 800 with Digital Holography

Abstract: The effects of chloride and thiosulfate ions on localized corrosion of alloy 800 are investigated through dynamical observation of the change in phase image of the diffusion layer during passive film breakdown using digital holography. The results indicate that solution chemistry has a significant effect on film breakdown and diffusion layer. The phase distribution changes at different applied potentials show that in the process of film breakdown, dissolution of metal ions from pitting is not remarkable in chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…2− lowered the pitting potential of Alloy 690, 26,33 Type 304 stainless steel, 27,28 UNS N08800 28,34,35 and Alloy 600 28 in solutions containing Cl − . The mechanism has been fused together by Newman 27 and Marcus 36 who claimed that, at higher CTCR, the passive film was damaged by Cl − and stabilized by the reduction of S 2 O 3 2− ions.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…2− lowered the pitting potential of Alloy 690, 26,33 Type 304 stainless steel, 27,28 UNS N08800 28,34,35 and Alloy 600 28 in solutions containing Cl − . The mechanism has been fused together by Newman 27 and Marcus 36 who claimed that, at higher CTCR, the passive film was damaged by Cl − and stabilized by the reduction of S 2 O 3 2− ions.…”
mentioning
confidence: 98%
“…(1) At high CTCR, the breakdown potential is significantly lowered, compared with breakdown potential in chloride-only solution, 15 For instance, previous experiments have indicated that S 2 O 3 2− lowered the pitting potential of Alloy 690, 26,33 Type 304 stainless steel, 27,28 UNS N08800 28,34,35 and Alloy 600 28 in solutions containing Cl − . The mechanism has been fused together by Newman 27 and Marcus 36 who claimed that, at higher CTCR, the passive film was damaged by Cl − and stabilized by the reduction of S 2 O 3 2− ions.…”
mentioning
confidence: 99%
“…and Cl − on passive film degradation has been reported on alloys 690, 131,132 304 SS, 59,65,133,134 316 SS, 65,134 Alloy 800, 59,135,136 304L SS, 137 and Alloy 600, 59,138,139 as a decreased pitting potential is observed in Cl − +S 2 O 3 2− solutions, compared with Cl − -only or S 2 O 3 2−only solutions. The combined effect of S 2 O 3 2− and Cl − is observed in cases where Cl − /S 2 O 3 2− concentration ratio is high, as discussed in S 2 O 3 2− section.…”
Section: Interactions Of CL − and S X With Passive Film At High And L...mentioning
confidence: 94%
“…The image processing method for reconstructing holograms has been used thus far and has played an important role in corrosion and electrochemical studies. DH reconstruction technology has been widely used, such as in situ observation of the transient concentration gradient in the diffusion layer (Yuan et al , 2008), local corrosion at the interface (Li et al , 2012), the diffusion layer during the rupture processes of the passive film of 800 alloy (Xia et al , 2015), anodic dissolution processes in neutral and acidic sulfate solutions (Hu et al , 2016), monitoring reactions at the interface of lithium-ion batteries (Lai et al , 2017) and the effect of magnetic fields on the IGC of nickel 690 in sodium chloride solution (Xu et al , 2022).…”
Section: Application Of Holographic Techniques In the Corrosion Studiesmentioning
confidence: 99%